Framework of integrating algebraic thinking in problem based learning via online environment for school students - Mustaffa, N. (2018)
Algebraic thinking is a very important skill that should be mastered by students at an early stage before learning algebra. However, algebraic thinking is not emphasized in learning algebra. The traditional approach for teaching algebra, which involved writing and solving equations according to the rules of mathematics, is taught procedurally and in isolation from other mathematical domains, hence towards real-world application of learning mathematics. In this paper, we conducted a study that integrated the students' algebraic thinking into the problem-based learning (PBL) process. Qualitative data from a learning task, namely which consisted of teaching notes, self-readings, reflections, self-evaluations, evaluation of scenario problems, task-based interview transcripts, and task-based interview notes were used to explore the acquisition of algebraic thinking. Accordingly, the framework that integrates students' algebraic thinking with the PBL process is expected to assist teachers in enhancing the effectiveness of teaching and learning of algebra and can potentially serve as a basis for developing algebraic thinking among school students, particularly at lower secondary level.